2008
DOI: 10.1521/ijgp.2008.58.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Client Perception of Therapeutic Factors in Group Psychotherapy and Growth Groups: An Empirically-Based Hierarchical Model

Abstract: To assess group participants' perceptions of therapeutic factors, we developed an extensive questionnaire of 155 items that was administered to 489 members of 78 psychotherapy and growth groups of client-centered/experiential, psychoanalytic, behavioral, Gestalt and drama- and bodily oriented orientations. Using multivariate analyses we found a model that reveals the structure and connections of therapeutic factors as they are differentiated in the experience of the group members. Our model encompasses three h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 31 publications
2
30
0
3
Order By: Relevance
“…Additionally, participants were recruited from three counselor education programs, unlike some studies (e.g., Furr & Carroll, 2003;Luke & Kiweewa, 2010;Robson & Robson, 2008) that recruited participants from a single institution=program. Third, although several categorization schemes exist for the study of therapeutic factors in groups (e.g., Bloch et al, 1979;Dierick & Lietaer, 2008) no such scheme exists for the study of similar factors in experiential groups. The growth factors taxonomy developed for purposes of this study has the potential to assist in future studies of growth factors associated with experiential group participation.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Additionally, participants were recruited from three counselor education programs, unlike some studies (e.g., Furr & Carroll, 2003;Luke & Kiweewa, 2010;Robson & Robson, 2008) that recruited participants from a single institution=program. Third, although several categorization schemes exist for the study of therapeutic factors in groups (e.g., Bloch et al, 1979;Dierick & Lietaer, 2008) no such scheme exists for the study of similar factors in experiential groups. The growth factors taxonomy developed for purposes of this study has the potential to assist in future studies of growth factors associated with experiential group participation.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Employing a different methodological approach that relied on multiple sources for item generation, Dierick and Lietaer (2008) developed an extensive questionnaire with 155 items to reveal a hierarchical model of the structure and interconnectedness of the therapeutic factors. Based on rating data subsequently collected from 489 members of 78 psychotherapy and growth groups, the complex hierarchical model includes 28 basic scales that are organized into seven main scales associated with two higher order dimensions (Relational Climate includes the main scales of Group Cohesion, Interactional Confirmation, and Cathartic SelfRevelation; Psychological Work includes the main scales of SelfInsight and Progress, Observational Experiences, Getting Directives, and Interactional Confrontation).…”
Section: The Interdependence Of Therapeutic Factorsmentioning
confidence: 99%
“…The authors provide an argument that validity for these numerous TFs was determined by their grounded context, empirically derived structure, importance ratings, and correlations with outcome measures. However, the length of the questionnaire developed by Dierick and Lietaer (2008) is likely to be a practical deterrent to many clinicians and researchers. Bednar and kaul (1994) observed that greater precision in both the definition and measurement of group process elements is necessary to advance the research and practice of group therapy.…”
Section: The Interdependence Of Therapeutic Factorsmentioning
confidence: 99%
“…Many have been designed to specifically evaluate the presence of Yalom’s 11 factors [6,7,23-27]. More recently, Dierick and Lietaer [28], developed a questionnaire to investigate therapeutic factors across an extensive range of group therapies from the client’s perspective. Participants were diverse and represented inpatients and outpatients, as well as students and trainee psychotherapists.…”
Section: Introductionmentioning
confidence: 99%